Effects of Purple Rice Bran Genotype Kum Doi Saket (Oryza sativa L. ssp. indica) on Skeletal Muscle Glucose Transport System in Diabetic Rats - Sopida Apichai (เชียงใหม่ : บัณฑิตวิทยาลัย มหาวิทยาลัยเชียงใหม่, 2020)
Thai purple glutinous rice genotype Kum Doi Saket (Oryza sativa L. ssp. indica) is a famous local cultivar of rice in the Northern of Thailand that contains a much higher content of anthocyanins and gamma oryzanol in the aleurone layer. Anthocyanins, the major subgroup of flavonoids responsible for the blue, purple and red color plant tissue, have been displayed various biological actions including antioxidant, anti-inflammatory, antihyperlipidemic, and also antihyperglycemic actions. However, little is known regarding its potential effects on skeletal muscle, the major site of glucose disposal. Therefore, this present study aimed to investigate the anti-diabetic effect and to explore the underlying molecular mechanisms of action of this purple glutinous rice bran via focusing on skeletal muscle glucose transport system in both type 1 and type 2 diabetic rat models.